Diagnosa Preeklampsia pada Ibu Hamil Menggunakan Sistem Informasi Berbasis Web - Fajaria Nur Aini; Melyana Nurul Widyawati; Bedjo Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to produce a preeclampsia diagnostic system online and to determine the difference in the speed of time required to diagnose preeclampsia using a web-based information system with a manual system. This research method is to arrange a framework with a quasi experimental research design with a post test only with control group. This research was conducted at the Community Health Center. The results showed that the majority of respondents were healthy pregnant women namely in the intervention group of 20 pregnant women (30.30%) and in the control group of 15 pregnant women (22.73%). The smallest number of diagnoses is in the case of superimposed preeclampsia. Web-based information systems are also able to increase diagnostic speeds to 7.21%. Statistical test results using the Independent T-Test obtained a P-value of 0.041 <0.05 (Î±). Conclusion, there is a difference in the time of diagnosis of preeclampsia using a web-based information system with a manual system. Keywords: Diagnosis, Preeclampsia, Information Systems, Web